Tipologi Kepribadian Bob A. Sitorus dalam Kumpulan Puisi Haru Hara: Kajian Psikoanalisis Carl Gustav Jung - Kuansah, Hidayat Apri (Multiverse: Open Multidisciplinary Journal, 2024)
This research aims to determine the personality of Bob A. Sitorus and the factors influencing his personality in the poetry collection "Haru Hara." The study employs a qualitative descriptive method to clearly and thoroughly describe and explain the data. The primary source of data is the book "Haru Hara," published by Obelia Publisher in 2023. Data collection involved listening and note-taking techniques, and the analysis was conducted using Carl Gustav Jung's Psychoanalytic theory. The results indicate that Bob A. Sitorus's personality can be understood through both conscious and subconscious realms, consisting of mental function and mental attitude. His personality type is identified as feeling-introverted. The unconscious structure is divided into the personal unconscious, including rational thinker aspects, and the collective unconscious, represented by the anima-archetype. Factors influencing his personality are personal unconscious elements such as maturity, love motives, and frustration, as well as collective unconscious elements like biological and religious factors.